Perencanaan Sistem Proteksi Kebakaran Pada Gedung A Universitas PGRI Palembang - Ginta Pranata Putra; Emidiana Emidiana; Yudi Irwansi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
: Fire is one of the most detrimental hazards to the community, therefore a fire prevention system is needed to reduce the impact and losses caused by fire. This study aims to design a fire protection system that has a high level of reliability, capable of detecting various types of fires, this study aims to find out whether the provision of equipment in building A of Universitas PGRI Palembang has met the requirements according to the technical requirements of the fire protection system in buildings and the environment according to the regulation of the Minister of Public Works No.26/PRT/M/2008. The planning of the fire protection system in building A of the University of PGRI Palembang includes, planning the detector system, sprinklers, fire alarms, water volume and pumps. The results of the planning of this fire protection system are 22 detector points, 50 sprinkler points, a water volume of 190 m3, a water tank volume of 164 m3, a pump power of 112 kW, and a GWT capacity of 92 m3.